THE INFLUENCE OF LISTENING TO ENGLISH SONGS ON UNIVERSITY STUDENTS’ LANGUAGE SKILLS: A MIXED-METHODS STUDY OF ENGLISH EDUCATION STUDENTS IN PALANGKA RAYA - Julianthi Zefana Silitonga; Erma Sujiyani; Muhammad Subhan Fikri; Lesly Martha Cecylia Meka (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
English songs are widely used as informal learning resources and may influence students’ language development through both linguistic exposure and affective engagement. This study aims to investigate students’ perceptions of the influence of listening to English songs on their language skills in the English Education Study Program at the University of Palangka Raya. The study employed an explanatory sequential mixed-methods design. Quantitative data were collected through a questionnaire administered to seventh-semester students from the 2022 cohort(N=50). The instrument was tested for validity and reliability using Cronbach's alpha before being analyzed through descriptive statistics. Based on the quantitative results, ten students (N=10) were purposively selected for semi-structured interviews to gain deeper insights. Interview data were analyzed using thematic analysis. Quantitative findings reveal that 94% of students had positive perceptions, while 6% reported negative views regarding the use of English songs in language learning. Qualitative results revealed that listening to English songs supported vocabulary development, listening comprehension, pronunciation, speaking confidence, and overall language improvement. However, some students viewed songs primarily as entertainment and reported challenges, including distractions, exposure to informal language, and mismatches with their learning preferences. Overall, the study indicates that English songs can serve as a beneficial supplementary medium for language learning, depending on learners’ preferences and the extent of instructional integration.